Establishing a Marine Gravimeter Test Site in the South China Sea to Validate the Performance of Different Marine Gravimeters - Yuan Yuan; Zhaocai Wu; Jinyao Gao; Zhongshan Jiang (Remote Sensing)
Marine gravity anomalies play an important role in geophysics applications. To observe high-precision and high-resolution gravity anomalies, a high-performance marine gravimeter is key. At present, the marine gravimeters widely used in the world have different measurement principles, such as the two-axis stable platform gravimeter, gimbaled inertial navigation gravimeter, and strapdown gravimeter. However, the performances of marine gravimeters with different measurement principles show different precision levels in real applications. A synchronized comparison test on the same platform is the most direct method for evaluating their performance, which is a relative analysis method. To absolutely evaluate the performance of different kinds of marine gravimeters, a new method is presented to remove the residual noise from the measured free air gravity anomaly to establish an “air truth” free air gravity anomaly. Synchronous measurements with different gravimeters were carried out in the north area of the South China Sea, measured three times over a round trip, and the highest-precision free air gravity anomaly measured by GT-2M, SAG-2M, and ZL11-1A was chosen to establish the “air truth” free air gravity anomaly. The external consistency of the free air gravity anomaly upon the removal of residual noise of frequencies 0.03 Hz to 0.06 Hz improved, and the three separate standard free air gravity anomalies of each gravimeter were the same with no deviation. The weighted result of the three average values of GT-2M, SAG-2M, and ZL11-1A is the established “air truth” free air gravity anomaly, which can be used as a standard to estimate the performance of marine gravimeters with different kinds of principles.